2015
DOI: 10.1186/s13195-015-0164-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impact after short-term exposure to different proton pump inhibitors: assessment using CANTAB software

Abstract: IntroductionStudies have shown that proton pump inhibitors (PPIs) increase the brain burden of amyloid-beta (Aβ) and also create vitamin B12 deficiency. However, these two phenomena have deleterious effect on cognition and Alzheimer’s disease (AD). Since the use of PPIs has increased tremendously for the last few years, it is of great public health importance to investigate the cognitive impact of PPIs. Hence, the purpose of this study was to investigate the degree of neuropsychological association of each PPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 50 publications
0
46
0
2
Order By: Relevance
“…It was demonstrated that a statistically significant reduction occurred in sensorimotor ability, visual memory and learning, reaction time, rapid visual information processing, and spatial working memory in intervention groups . Some variance in results per PPI medication subtype was observed, with omeprazole demonstrating the most significant reduction in cognitive function (seven significant subtest reductions) and esomeprazole demonstrating the least (three significant subtest reductions) . However, all intervention groups demonstrated a general reduction in assessment performance when compared to the placebo group.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It was demonstrated that a statistically significant reduction occurred in sensorimotor ability, visual memory and learning, reaction time, rapid visual information processing, and spatial working memory in intervention groups . Some variance in results per PPI medication subtype was observed, with omeprazole demonstrating the most significant reduction in cognitive function (seven significant subtest reductions) and esomeprazole demonstrating the least (three significant subtest reductions) . However, all intervention groups demonstrated a general reduction in assessment performance when compared to the placebo group.…”
Section: Resultsmentioning
confidence: 97%
“…The systematic search strategy identified 1928 unique articles, 1895 of which were excluded during title and abstract screening. Thirty‐three remaining full text articles were assessed for eligibility, and of these, 11 met the inclusion criteria for this systematic review . Reasons for study exclusion are documented using the PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPIs were previously reported to impair the immunity function of leukocytes . Furthermore, patients’ cognitive functions can be affected by PPIs . Dementia patients are likely to be vulnerable to this complication because of a high likelihood of dysphagia, impairment of the gag reflex, and decreased levels of consciousness status and immunity .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GID is associated with aging populations [59]. However, one cannot dismiss the possibility that medications elderly patients take may contribute to GID, and, in fact, an association between pump inhibitors and cognitive impairment has recently been reported [60,61]. Of note, Parkinson disease has also been associated with gastrointestinal dysfunction [62].…”
Section: Discussionmentioning
confidence: 99%